(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
This article reviewed Western and Eastern literature and research into worldly and divine factors that improve personality, but found that not enough attention was paid to the harmony of humanity and divinity. Therefore, it is important to study the significance of the harmony of humanity and divinity in the spiritual development of man. This article is based on the fact that in Eastern philosophy, humanity and divinity are dialectically related realities.